Global research trends and hotspots of oxidative stress in diabetic retinopathy (2000-2024) - Du, Kejie; Liu, Yichong; Zhao, Xintong; Wang, Haowen; Wan, Xiaomei; Sun, Xiaoyan; Luo, Wenjuan (Frontiers in Endocrinology, 2024)
Introduction Oxidative stress has been identified as a major contributor to the pathogenesis of DR, and many diagnostic and therapeutic strategies have been developed to target oxidative stress. Our aim was to understand the contribution of the country of origin of the publication, the institution, the authors, and the collaborative relationship between them. Methods We performed a bibliometric analysis to summarize and explore the research hotspots and trends of oxidative stress in the DR. Results We observe an upward trend in the number of posts on related topics from year to year. Expanding on this, Queens University Belfast is the most influential research institution. Current research hotspots and trends focus on the mechanism of autophagy and NLRP3 inflammasome's role in oxidative stress in DR. Discussion We conducted a multi-dimensional analysis of the research status of oxidative stress in diabetic retinopathy through bibliometric analysis, and proposed possible future research trends and hotspots.